Chest Computed Tomography Scores of Severity Are Associated with Future Lung Disease Progression in Children with Cystic Fibrosis - Sanders, Don B. (American Thoracic Society, 2011)
Rationale: Most children with cystic fibrosis (CF) experience a slow decline in spirometry, although some children continue to be at risk for more significant lung disease progression. Chest computed tomography (CT) scans have been shown to be more sensitive to changes in lung disease than spirometry and may provide a means for predicting future lung disease progression. Objectives: We hypothesized that Brody chest CT scan scores obtained in 2000 in a prospectively monitored cohort of children with CF would be associated with the most recent measures of lung disease severity. Methods: Brody chest CT scan scores were calculated for 81 children enrolled in the Wisconsin CF Neonatal Screening Project. Multivariable linear regression was used to determine associations between Brody scores and the most recent (age 21 yr or June 30, 2010, whichever was later) measures of CF lung disease. Measurements and Main Results: The mean observation time after the chest CT scan was 7.5 years. Brody chest CT scan scores were significantly associated with the most recent measures of spirometry (P < 0.001) and Wisconsin and Brasfield chest radiograph scores (P < 0.001). The strength of this association was much stronger than spirometry obtained near the time of the chest CT scan (P < 0.01) but not chest radiograph scores. Conclusions: Chest CT scan scores are associated with future lung disease severity, and quantitative chest imaging (chest CT scan and chest radiograph scores) is more strongly associated with future lung disease severity than measures of spirometry. These findings may help clinicians identify patients at risk of future lung disease progression.